The effect of auriculotherapy on improving sleep quality in postmenopausal women aged 45-60 years: A clinical trial study - Mona Eidani; Simin Montazeri; Parvaneh Mousavi; Mohammad Hosein Haghighizadeh; Mahboubeh Valiani (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Menopause is one of the developmental stages of women. One of the most common problems during this period is sleep disorders. Sleep disorders can affect the quality of life of these people. To improve sleep disorders, auriculotherapy has received less attention due to its low cost and effectiveness, and side effects. Therefore, the aim of this study was to determine the effect of auriculotherapy on improving sleep quality in postmenopausal women aged 45-60 years. MATERIALS AND METHODS: The present study is a clinical trial study that was performed on 82 postmenopausal women aged 45-60 years under the auspices of health centers in Mahshahr city, Iran from 2021-2022. Women with inclusion criteria were randomly divided into two groups (intervention and control). The intervention group underwent auriculotherapy for 4 weeks. The St. Petersburg Sleep Quality Questionnaire was completed by both groups at the beginning and 4 weeks after the start of the intervention. Finally, the data were analyzed by SPSS software version 22 and independent t-test, paired t-test and Chi-square test. RESULTS: At the beginning of the study, both groups were homogeneous in terms of demographic variables. The results of data analysis using independent t-test showed that before the intervention, mental quality (P = 0.513), length of incubation period (P = 0.285), sleep duration (P = 0.121), sleep efficiency (P = 0.513), sleep disorders (P = 0.685), use of sleeping pills (P = 0.530), daily functioning (P = 0.60), and overall sleep quality score (P = 0.30) in the control and intervention groups were not statistically significant. However, comparing the mean scores after the intervention in the control and intervention groups showed that mental quality (P < 0.001), incubation period (P < 0.001), sleep duration (P < 0.001), sleep efficiency (P < 0.001), sleep disorders (P < 0.001), use of hypnotics (P = 0.002), daily functioning (P = 0.001), overall sleep quality score (P < 0.001), sleep duration (P = 0.822), sleep efficiency (P = 0.889), sleep disorders (P = 0.889), use of sleeping pills (P = 1.00), daily performance (P = 0.767), overall sleep quality score (P = 0.69) were statistically significant between the two groups. In-group comparison using paired t-test in the control group showed that mental quality (P = 0128), length of the incubation period (P = 1.00), and before and after the intervention did not differ significantly in the mean scores. However, a within-group comparison in the intervention group showed that mental quality (P < 0.001), incubation period (P < 0.001), sleep duration (P < 0.001), sleep efficiency (P < 0.001), sleep disorders (P = 0.003), use of sleeping pills (P = 0.007), daily functioning (P < 0.001), and overall sleep quality score (P < 0.001) before and after the intervention had a significant difference in the mean scores. CONCLUSION: The results showed that auriculotherapy has significant effectiveness in improving the quality of sleep, and its dimensions and can be used as an effective method in this area that can be implemented at a low cost and easily. According to reports from participants and previous studies in this field, auriculotherapy did not have any side effects and can be used as a safe way to improve sleep quality.